2009
DOI: 10.1111/j.1442-200x.2009.02859.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of allergic sensitization and gastroesophageal reflux disease in children with recurrent croup

Abstract: GER and atopy should be investigated in patients with recurrent spasmodic croup. Recurrent croup is a non-specific manifestation of atopy. Patients with atopy should be followed closely for developing bronchial asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 20 publications
0
28
0
2
Order By: Relevance
“…Two case-control studies, Arslan et al and Contencin and Nancy, found a statistically significant increase in reflux in patients with recurrent croup, from a symptomatic standpoint and with esophageal and pharyngeal pH data. 4,11 However, regardless of study design, this association does not establish causality. Patients treated with reflux medications appear to demonstrate a reduced incidence of croup or croup symptoms, and these studies are less heterogeneous, meaning that the combined results are more conclusive.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Two case-control studies, Arslan et al and Contencin and Nancy, found a statistically significant increase in reflux in patients with recurrent croup, from a symptomatic standpoint and with esophageal and pharyngeal pH data. 4,11 However, regardless of study design, this association does not establish causality. Patients treated with reflux medications appear to demonstrate a reduced incidence of croup or croup symptoms, and these studies are less heterogeneous, meaning that the combined results are more conclusive.…”
Section: Discussionmentioning
confidence: 94%
“…Of the 15 articles included in this review, 12 are cross-sectional studies that describe the prevalence of reflux in patients with recurrent croup. 3,4,6,[9][10][11][12][13][14][15][16][17][18][19] These are summarized in Table I. The reported prevalence of GERD in these studies ranges from 5% (Jabbour et al) to 87% (Hoa et al), and studies that used direct laryngobronchoscopy findings to define GERD tended to report higher prevalence than those that relied on clinical presentation and history.…”
Section: Resultsmentioning
confidence: 99%
“…These sur veys suggest that further observation of children with recurrent subglottic laryngitis is necessary to potentially screen for asthma [18]. The possi ble mechanisms that explain the increased risk of asthma in children with a history of acute subglottic laryngitis include a smaller diameter of the airways (both central and peripheral), more frequent atopy, gastroesophageal reflux, bronchial hyperresponsiveness and common CD14 gene polymorphisms [19][20][21][22]. In adulthood, cases of acute subglottic laryngitis are very rare [23].…”
Section: Epidemiologymentioning
confidence: 99%
“…Whereas there is no definitive definition, atypical croup is usually described as frequently recurrent croup episodes often occurring in children outside the expected age of presentation. Atypical croup is less associated with viral entities and more commonly described as an allergic or inflammatory response . Whereas reports suggest that anywhere from 25% to 100% of these children have other airway lesions, there are some children who continue to suffer from atypical croup despite having no evidence of airway anomalies.…”
Section: Introductionmentioning
confidence: 99%